Calculation of Full Energy Peak Efficiency for HPGe Detector Using Monte Carlo Method - B. Kadhim, Alaa; S. Fadhil, Sura (Iraqi Journal of Science, 2023)
This research presents results on the full energy peak efficiency of a high purity germanium (HPGe) detector from point source as a function of photon energy and source-detector distance. The directions of photons emitted from the source and the photon path lengths in the detector were determined by Monte Carlo technique. A major advantage of this technique is the short computation time compared to the experiments. Another advantage is the flexibility for inputting detector-related parameters (such as source–detector distance, detector radius, length and attenuation coefficient) into the algorithm developed, thus making it an easy and flexible method to apply to other detector systems and configurations. It has been designed and written the program for this computational. The results of the full energy peak counting efficiency were compared with the published results. It appears in a good agreement with quantity and behavior.